2014
DOI: 10.3109/1547691x.2014.978056
|View full text |Cite
|
Sign up to set email alerts
|

Association between lower frequency of R381Q variant (rs11209026) in IL-23 receptor gene and increased risk of recurrent spontaneous abortion (RSA)

Abstract: Recurrent spontaneous abortion (RSA) is defined as three or more consecutive spontaneous abortions before the 20th week of gestation. The purpose of the present study was to investigate the association between a functional single nucleotide polymorphism (SNP) in the interleukin (IL)-23 receptor gene (IL-23R; rs11209026, 1142 G wild type ! A reduced function, Arg381Gln, R381Q) and RSA. For the study, 200 RSA patients (confirmed using established diagnostic criteria) and 200 normal individuals in fertility and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The proportions of T H 17 (CD4 + IL-17A + ) cells in the peripheral blood and decidua were found to be significantly higher in unexplained RSA subjects than in normal pregnant women (Tavasolian et al 2014). The pro-inflammatory features of IL-23 have been linked with T H 17 cell responses through the expansion and maintenance of T H 17 cells (Abdollahi et al 2015). In that study, the association between R381Q variant and recurrent spontaneous abortion was investigated and a significant difference was found between the case and control group subjects with regard to a presence of the R381Q variant.…”
Section: Role For R381q Variant In Non-gastrointestinal Autoimmune DImentioning
confidence: 95%
See 2 more Smart Citations
“…The proportions of T H 17 (CD4 + IL-17A + ) cells in the peripheral blood and decidua were found to be significantly higher in unexplained RSA subjects than in normal pregnant women (Tavasolian et al 2014). The pro-inflammatory features of IL-23 have been linked with T H 17 cell responses through the expansion and maintenance of T H 17 cells (Abdollahi et al 2015). In that study, the association between R381Q variant and recurrent spontaneous abortion was investigated and a significant difference was found between the case and control group subjects with regard to a presence of the R381Q variant.…”
Section: Role For R381q Variant In Non-gastrointestinal Autoimmune DImentioning
confidence: 95%
“…Abdollahi et al (2015) reported that the number and activity of both circulating T H 17 cells and in vitro (ex vivo)-differentiated T H 17 cells did not differ between G and A allele carriers. This finding supported the belief for a major role for IL-23 in generation of T H 17 cell effector responses during tissue inflammation (rather than in systemic inflammation) and demonstrated the importance of IL-23 in mediating T H 17 effector responses in humans.…”
Section: R381q Polymorphism: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, Th17 cells can be induced by IL-6, IL-1b, and TNF-a, which are abundant in the inflamed joint of patients with active disease, and are directly involved in cartilage and bone destruction. Therefore, IL-17 is described as an inflammatory cytokine which has a role in many inflammatory conditions [Abdollahi et al, 2015[Abdollahi et al, , 2016.…”
Section: Regulation Of Effector T-helper Cellsmentioning
confidence: 99%
“…Recurrent miscarriage (RM), defined as the loss of three or more consecutive pregnancies in the first trimester of pregnancy, affects $1-2% of fertile women (Abdollahi et al, 2014;Matter & Sharif, 2013). At present, there are some accepted etiologies for RM (Ford & Schust, 2009) (Figure 1), including parental chromosomal abnormalities, untreated hypo-thyroidism, uncontrolled diabetes mellitus, certain uterine anatomic abnormalities and anti-phospholipid antibody syndrome (APS), endocrine disorders, heritable/acquired thrombophilias, immunologic abnormalities, infections and environmental factors.…”
Section: Introductionmentioning
confidence: 99%